STUDY ON EFFECT OF SUBSTRATE CONCENTRATION AND SAMPLING SITES ON INORGANIC NITROGEN TRANSFORMATION RATES IN COASTAL AQUACULTURE AREA OF HAI PHONG - Hao, Do Manh; Anh Tuyet, Dao Thi; Hiep, Le Minh; Huyen, Le Thanh (Vietnam Journal of Marine Science and Technology, 2014)
The regulation effect of substrate concentration and sediment features on nitrification and nitrate reduction potentials was assessed based on study results at 6 sites with different sediment characteristics and aquaculturing options in two coastal culturing zones in Hai Phong city, in April and August 2013. Nitrification and nitrate reduction rates were measured in slurries of field samples and enrichment experiments using the acetylene inhibition techniques. Nitrification and nitrate reduction rates ranged from 1.5 - 8.6mgN/g wet weight-1h-1 và 11.0 - 54.0mgN/g wet weight-1h-1, respectively. Both of these processes depended on substrate concentrations and sampling sites. Substrate availability stimulated inorganic nitrogen transformation activity but only within retricted range, further increase in substrate availability inhibited the activities. The thresholds of substrate concentrations for nitrification and nitrate reduction were in ranges of 0.55 - 1.00 mgN/l and 1.53 - 2.82 mgN/l, respectively.